2019
DOI: 10.1021/acsabm.9b00809
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4-ethylenedioxythiophene) (PEDOT) Coatings for High-Quality Electromyography Recording

Abstract: Conductive polymer coatings on metal electrodes are an efficient solution to improve neural signal recording and stimulation due to their mixed electronic-ionic conduction and biocompatibility.To date only a few studies have been reported on conductive polymer coatings on metallic wire electrodes for muscle signal recording. These studies mainly deal with testing of electrodes for acute recording during anaesthesia. Chronic muscle signal recording in free-walking animals offers more challenges for the electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 104 publications
0
30
0
Order By: Relevance
“…Besides PSS, other dopants such as para-toluene sulfonate, trifluoromethanesulfonate, and inorganic anions are used in PEDOT-based conducting polymers for wearable electronics and bioelectronics ( Figure S6, Supporting Information). [33,49,52] We produced PEDOT:Tos and PEDOT:OTf films via chemical polymerization, which showed electrical conductivities of ≈1600 and ≈2200 S cm −1 , respectively. Inter-estingly, the healing experiments showed that these materials can also be healed repeatedly by water, similarly to PEDOT:PSS (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides PSS, other dopants such as para-toluene sulfonate, trifluoromethanesulfonate, and inorganic anions are used in PEDOT-based conducting polymers for wearable electronics and bioelectronics ( Figure S6, Supporting Information). [33,49,52] We produced PEDOT:Tos and PEDOT:OTf films via chemical polymerization, which showed electrical conductivities of ≈1600 and ≈2200 S cm −1 , respectively. Inter-estingly, the healing experiments showed that these materials can also be healed repeatedly by water, similarly to PEDOT:PSS (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…− is adopted as the dopant for PEDOT in electropolymerization because to small dopants generally have better electrochemical properties with respect to larger ones (e.g., PSS). [52][53][54][55] In this case, upon one cut, the water droplet cannot restore the initial current of PEDOT:ClO 4 film, and only induces a transient ionic current flow similar to that observed in PEDOT:PSS films soaked in sulfuric acid for 3 days (Figure 5a). The difference between the water-enabled healing abilities of these various conducting polymers is probably based on their ability to swell in water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bihar et al reported on PEDOT:PSS electrodes inkjet-printed on paper for ECG recording [7]. Rossetie et al coated electrochemical stainless steel microwires with PEDOT:PSS for electromyogram recording in rats [8]. Zahed et al manufactured PEDOT:PSS loaded laser-induced graphene (LIG) electrodes for ECG recording [9].…”
Section: Introductionmentioning
confidence: 99%